A growth/annealing equilibrium model for helium-induced nanostructure with application to ITER. (May 2019) - De Temmerman, G.; Doerner, R.P.; Pitts, R.A.
Highlights: The formation of W fuzz in ITER is discussed. An analysis of existing data shows that the fuzz annealing kinetics can be described by a diffusive-like kinetics law. The proposed growth/annealing equilibrium model accounts for ELM-induced erosion and temperature excursion on fuzz growth and annealing. An equilibrium thickness exists above which fuzz annealing dominates for a given ELM energy density. Abstract: It is now well-known that under exposure to a helium (He) plasma at elevated temperatures, a tungsten (W) surface is modified by the growth of a fibreform nano-structure referred to as "fuzz". Formation of W fuzz occurs when a specific set of conditions are met and raises concerns for the behaviour of the ITER W divertor targets. The key open question remains, however, of whether or not fuzz will actually form in ITER. An analysis of existing data shows that the fuzz annealing kinetics can be described by a diffusive-like kinetics law. A growth/annealing equilibrium model is then proposed to take into account Edge Localized Mode (ELM)-induced erosion and the effect of the transient temperature excursion on fuzz growth and annealing. In addition, both the decrease of fuzz erosion rate and thermal conductivity with increasing thickness are treated consistently. The main finding is that as fuzz grows thicker, its thermal conductivity decreases and peak temperature attained during an ELM increases. Given the competition between growth and annealing rates, an equilibrium thickness exists above which fuzz annealing dominates for a given ELM energy density. In the absence of ELMs, the fuzz thickness would increase with the typical t 0.5 time dependence.